Implementation Of Sharia Law On Patient Medical Services In Certified Sharia Hospitals: A Literature Review - Indah Khairunnisa; Kusbaryanto Kusbaryanto (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
This Research uses literature review method, and the aim of this research is to find out how the Implementation of Sharia Law on  patients services in Sharia Hospitals. The articles that used in the research are articles published between 2011-2021. Article searches were conducted in four databases including; Pubmed, Mendeley, Google Scholar and scienceDirect. This study used the PRISMA protocol. The review covers articles that discuss about the concept of sharia law and how it is implemented in patient care in certified Sharia Hospitals. From the articles reviewed, it was found that the implementation of sharia law in hospitals is related to the application of Maqashid Sharia which consists of five main points; Hifdz Ad-Din, Hifdz An-Nafs, Hifdz Al-Aql, Hifdz An-Nasl, and Hifdz Al-Mal. The implementation of sharia law in hospitals is also related to increasing patient satisfaction.